1986
DOI: 10.1111/j.1440-169x.1986.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Role of Astral Rays in Pronuclear Migration in Sand Dollar Eggs by the Colcemid‐UV Method

Abstract: The formation and migration of the sperm aster, and the migration of male and female pronuclei during fertilization were investigated in the eggs of the sand dollar, CZypeaster japonicus using the Colcemid-UV method. When an egg in Colcemid sea water was irradiated locally with UV light (about 365 nm wavelength) at a limited region containing sperm head, a sperm aster formed in this region, and migrated to the center of the UV-irradiated region during its formation. When the UV-irradiated region was displaced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
114
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(132 citation statements)
references
References 17 publications
(3 reference statements)
5
114
1
Order By: Relevance
“…The cellular basis of such a stabilizing effect is not understood, but it seems plausible that the microtubules extending from the centrosome are required, presumably by maintaining the centrosome in a near-centroid position (27). Directional changes initiated (and executed) in the cell periphery may lead to a gradual repositioning of the microtubule-organizing center by virtue of dynamic length changes of microtubules, as suggested by the elegant experiments of Hamaguchi and Hiramoto (37). Thus microtubules may be considered as sensors of directional changes that help maintain the centrosome in a position near the cell center where the microtubule system can respond quickly to rapid and sometimes gross changes in cell morphology in the course of cell movement.…”
Section: Resultsmentioning
confidence: 98%
“…The cellular basis of such a stabilizing effect is not understood, but it seems plausible that the microtubules extending from the centrosome are required, presumably by maintaining the centrosome in a near-centroid position (27). Directional changes initiated (and executed) in the cell periphery may lead to a gradual repositioning of the microtubule-organizing center by virtue of dynamic length changes of microtubules, as suggested by the elegant experiments of Hamaguchi and Hiramoto (37). Thus microtubules may be considered as sensors of directional changes that help maintain the centrosome in a position near the cell center where the microtubule system can respond quickly to rapid and sometimes gross changes in cell morphology in the course of cell movement.…”
Section: Resultsmentioning
confidence: 98%
“…In this case, the pulling force per microtubule increases as the length of the microtubule increases because the longer the microtubule, the more contact with cytoplasmic dynein (6). This length-dependent pulling mechanism was initially proposed by Hamaguchi and Hiramoto in sand dollar eggs (25). In a computer simulation assuming that the centrosome centration anchors are located throughout the cytoplasm, the in vivo profile of centrosome centration in C. elegans was reproduced (16).…”
mentioning
confidence: 91%
“…However, these cytoplasmic dyneins at the cortex may not be required for centrosome centration. In sand dollar eggs, centrosome centration occurs in a cortex-independent manner (25). In large amphibian eggs, the plus ends of microtubules do not reach the cell cortex in the traveling direction during centrosome centration (20).…”
mentioning
confidence: 99%
“…Laser microsurgery experiments in Fusarium solani or C. elegans suggested that this link corresponds to astral microtubules connecting the spindle poles with the cell cortex [6,7,8,9,10 ]. Although not the focus of this review, there are instances where pulling forces are exerted along the length of astral microtubules instead of at their plusend located at the cell cortex [11,12,13]. Work in several systems in recent years has increased our understanding of the basic principles governing spindle positioning and identified core molecular players and aspects of their mechanism of action.…”
mentioning
confidence: 99%